PEMETAAN MEDIA LOKAL ACEH; KEHADIRAN, TANTANGAN SERTARELASINYA DENGAN POLITIK LOKAL - Nellis Mardhiah (Universitas Teuku Umar, 2017)
Theoretically, the media and politics can not be separated. Media and politics are like two sides of the same coin in which each one requires another. This is what happened in Aceh. Media and political links are highly visible in the practice of the press in Aceh. The presence of the media in Aceh seems very much to serve the political ambition through the news. The practice of the press industry looks like it is thick with the nuances of interest, which is interestingly studied with the approach of political economy. Political economy theorists see that there are certain groups that control economic institutions that then affect other social institutions, including the media and the press. In other words, the mastery of economic institutions will lead to the mastery of almost all aspects of life, ranging from small things such as how to eat to big things like communication devices. The mastery is meant to perpetuate their economic power. In the context of Aceh specially post-enactment of the Law on Aceh Goverment. The presence of local media is not only a part of the vortex of information, but also present as part of local political democratization. This is the challenge of the media or the local press itself. Does the media capable of maintaining its independence in managing information? or actually engaging in political practices in favor of certain political groups? Keywords: Local Media, Political Economic Media, Elite Politic, Aceh.